Organization and Control of Lithuanian Literature Teaching in the Late Soviet Era - Vasiliauskas, Saulius (Colloquia, 2025)
Although the debate about the teaching of literature in Lithuanian schools continues to this day, a more detailed and critical discussion as well as reflection on the mechanisms of teaching and controlling literature in Soviet-era Lithuania has been still lacking. In an attempt to partially fill this gap, the article reconstructs the organization of teaching literature during the Soviet era, based on a variety of materials relevant to the research (archives, periodicals, textbooks, school curricula, testimonies by contemporaries, egodocuments, etc.). The article focuses on the period from the Thaw to the end of the Soviet era, when education underwent reforms. The article discusses leading institutions and personalities—the movers and shakers in the organization of literature teaching, the authors of literature textbooks and programs (for the upper grades), the context of the development of materials for school, as well as teachers‘ testimonies about the requirements for literature teaching and the development of materials for it. The aim is to present an extensive overview and systematization of the history of the development of Lithuanian studies content in the late Soviet era.